Penerapan Pendekatan Sains Teknologi Masyarakat Pada Materi Daur Air Dalam Meningkatkan Hasil Belajar Siswa Di Kelas VI SD Inpres 3/77 Bukaka Kabupaten Bone - Muhammad Darwis (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
This study uses a qualitative approach and type of classroom action research. The formulation of the problem from this study is whether the application of the Community Technology Science approach to water cycle material can improve the learning outcomes of class VI SD Inpres 3/77 Bukaka and how the process of applying the Community Technology Science approach to water cycle material in improving learning outcomes of grade VI SD Inpres students 3/77 Bukaka. The purpose of this study was to improve the learning outcomes of class VI SD Inpres 3/77 Bukaka on water cycle material through the application of the Community Technoogy Science approach, as well as improving the learning process / water cycle material through the application of the Science Technology Society class VI approach at SD Inpres 3/77 Bukaka . The object of this research is the sixth grade students of SD Inpres 3/77 Bukaka. Data collection techniques used are teacher and student observation, and documentation. Based on the results of the analysis and evaluation at the reflection stage, the results of the study show that the application of the Community Technology Science approach effectively improves the process / activity and learning outcomes in the Water Recycling material in each cycle of action.